Finding the impact of information sources a study on the political information efficacy and voting behavior of Filipino young voters in Metro Manila - Del Mundo, Rafael Joseph C.; Santos, Yhna Therese, P.; Peoro, Rolly Francis, C. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2019)
Young voters are an important voting bloc, especially in the Philippines because they not only hold a significant portion of the voting population, but they also represent the future voting culture of the country. In this regard, it is ideal that young voters are well-informed about election-related activities such as knowing about the profile and platforms of political candidates, schedule of the elections, the actual process of registration and voting, and many other important things. Consequently, knowing about one's confidence in their political knowledge is essential for effective engagement and participation in the election. It is in this light that this study focused on determining the impact of election information sources to young voters by identifying sources that are frequently use, reliable and influential. Furthermore, this study determined the Political Information Efficacy (PIE) or the confidence of young voters in their political knowledge as well as their voting behavior of information sources to the PIE and voting behavior of Filipino young registered voters was also one of the focus of this study.
The data gathered from the survey questionnaire and Focus Group Discussions (FGDs) revealed that election information sources young voters used the most are social media, television, parents and printed newspapers. With regard to the reliability, young voters find printed newspapers, parents, siblings, television, radio and online newspapers the most reliable. Lastly, in terms of information sources, they find social media, television, parents, siblings, printed newspapers and radio as the most influential.
As for the association or relationship of election information sources to the PIE and voting behavior of young voters, this study revealed that for usage frequency, the relationship was mostly positive but "very weak". However, in terms of reliability and influence, the association for the Political Information Efficacy and voting behavior of young voters was mostly negative and "very weak". This study also found out the PIE and voting behavior were positively associated.
In conclusion, in terms of usage, young voters will most likely use popular, readily available and easily accessible sources. As for reliability, sources are found to be reliable if these are readily available and accessible With regard to the influence, young voters agreed that these were the types that are readily accessible and available, offers content that are varied and extensive, uses prominent and influential personalities and those that provide direct and personal interactions.
Lastly, this study showed that the usage frequency of election information sources may have more positive impact to one's confidence in their political knowledge and political participation of young voters compared to the reliability and influence of information sources.
Thesis (Master of Library and Information Science)
Keywords: Voting behavior -- Young voters -- Metro Manila; Voting behavior -- Young voters -- Filipino -- Metro Manila